In-Service Training for Professionals - V. Ray Kurtz (Educational Considerations, 1974)
For truly effective inservice programs, first assess teachers' "felt needs" for additional preparation or updating in content and methodology, urges this educator, who's been involved with such activities for 11 years. Unfortunately, such assessment "is very seldom done." He describes its value.